Two-phase optimal planning of substation locating based on refined PSO algorithm - Yan, Si-Wei; Yao, Jian-Gang; Li, Feng-Tao; Wang, Xue-Jin; Liu, Juan (Dianli Xitong Baohu yu Kongzhi, 2010)
This paper proposes a two-phase optimal planning of substation locating based on refined particle swarm optimization (PSO) which introduces extremum disturbed operator. Firstly, the first-phase substation combination is obtained with refined PSO searching in the planning area; secondly, the surrounding geographical factors are considered in detail during which the invalid addresses are sorted out and the nearby districts are pitched on to form the second-phase substation combination. The efforts of geographical factors against target function are analyzed by means of fuzzy analysis hierarchy process. Thus the target function is amended, considering the investing and operating costs of incoming circuitries as well as out-coming ones to perfect planning results. An actual example certifies that the method raised in this paper could better satisfy the planning requirements.